Vegetation Transformations of Kujawy-Pomerania Region in the Last Twenty Years Period - Załuski, Tomasz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
This paper contents dynamic tendencies analysis results of Kujawy-Pomerania region (N Poland) for a 20-year time period. Acreage changes as well as structure and species composition transformations of forest and shrub vegetation (associations) and non-forest vegetation (alliances) were evaluated. Main factors influencing on regressive and progressive changes were set out. Analysis was relied on results of geobotanical research and observations of selected objects. Regressive changes were noted for i.a. thermophilous oak forests, dry and fresh coniferous forests, aquatic, halophytic, pasture vegetation, vegetation of Molinion and Cnidion meadows, heaths and xerothermic grasslands. Whereas progressive were observed in case of mixed coniferous forests, mesophytic shrubs, rush and tall herbs vegetation, fresh meadows and some ruderal communities.